Analisis Penerapan Sanksi Pidana Terhadap Pelaku Tindak Pidana Yang Mengoperasikan Kapal Penangkapan Ikan Tanpa Surat Izin Penangkapan Ikan - Pasya, Rafli; Mubarak, Ridho (Universitas Medan Area, 2025)
The problem in this study focuses on how the Legal Arrangements and Judges' Considerations in Criminal Sanctions Against Criminal Actors Who Operate Fishing Vessels Without a Fishing License in the Medan District Court Decision Number: 04/Pid.Sus-PRK/2020/PN.Mdn. This study aims to determine the Legal Arrangements and Judges' Considerations. The research method used in this study is normative juridical. the results of this study indicate that the Legal Arrangements are regulated in Articles 27, 28, and 93 of Law Number 31 of 2004 concerning Fisheries. The Judge's Considerations consist of legal considerations including, the Public Prosecutor's Indictment, Witness Statements, Expert Statements, Defendant's Statements, Evidence, Article 93 paragraph (1) Jo Article 27 paragraph (1) of the Republic of Indonesia Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries. And the aggravating and mitigating factors for the Defendant.